Avaliação da atividade turística sobre a composição e a distribuição das macroalgas marinhas nos recifes de Pirangi (Rio Grande do Norte, Brasil) - Azevedo, Carolina Angélica Araújo de (2011)
The reef area of Pirangi beach has been experiencing antropogenic actions, mainly due to tourism activity. In order to evaluate these effects, surveys on seaweeds were conducted at nine stations located over the fringing reef. Benthic community (seaweeds/corals) were identified using the photoquadrat method, with 50 meters random transects located paralleled to the coast. The general categories evaluated in each transect were: rock, sand, seaweeds, corals and mollusks. Data achieved were processed at Coral Point Count with Excel Extensions software. A total of 30 seaweed species, 5 coral species and 1 mollusk species were identified. There was a high dominance of short algae at stations with high tourism pressure, whereas frondose algae usually occurred at places without human interference. Seaweeds with the highest percent cover were composed by Sargassum vulgare (59%), Caulerpa racemosa (47%) and Dictyopteris delicatula (33%). Cluster analyses considering benthic organisms revealed five benthic features: (1) submersed area characterized by a diversified marine flora; (2) area with dominance of Caulerpa racemosa and presence of Millepora alcicornis; (3) area with high cover of Sargassum vulgare; (4) trampling area characterized by bare rocks, short algae and Zoanthus sociatus and (5) area with high coverage of Palythoa caribaeroum. Obtained data suggest that the studied area has been damaged by tourism activities. Furthermore, observed differences in algal communities may be a good indicator of ecosystem health of Pirangi reefs